2021
DOI: 10.1007/s11664-021-09202-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of MnO2 and AgNWs Co-Doped into an Activated Carbon Thin Film Electrode for Supercapacitors

Abstract: In this study, the properties of supercapacitors were improved by doping nanomaterials. Transition metal oxides (i.e., MnO 2 ) with Faraday's reduction-oxidation (redox) reaction and silver nanowires (AgNWs) with high conductivity were doped into activated carbon based material to prepare thin-film electrodes. The results indicated that doping with AgNWs can effectively improve the conductivity of the thin film electrode. A conductive network was constructed between activated carbon and MnO 2 , and the optimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Table 1 shows the advanced crystal structure parameters, along with the relevant experimental values [20] and calculated theoretical results [21–23]. It is found that there is a high agreement between the values, which indicates that this computational effort is meaningful.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Table 1 shows the advanced crystal structure parameters, along with the relevant experimental values [20] and calculated theoretical results [21–23]. It is found that there is a high agreement between the values, which indicates that this computational effort is meaningful.…”
Section: Resultsmentioning
confidence: 95%
“…Table 1 shows the heats of formation for seven compounds, along with the theoretical values [21–24] and experimental results [25]. When Zn is doped into η ′‐Cu 6 Sn 5 , the predicted heats of formation are all negative, indicating that η ′‐Cu 6 Sn 5 ‐based IMCs are all stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Electrodes of activated carbon fibres with well-aligned tin oxynitride nanorod arrays have shown a high specific capacitance of 673 F/g at 1 A/g and a cycling stability of 99% at 5 A/g for 2000 cycles in 1 M H 2 SO 4 electrolyte [74]. Activated carbon was doped with MnO 2 and silver nanowires in order to improve the conductivity of the thin film electrode, resulting in a specific capacitance of 1021 F/g, a 325% increase from the undoped activated carbon [75]. Another recent study presented the direct fabrication of hierarchical porous carbon/silicon carbide (HPC/SiC) composite from bamboo waste raw biomass via a facile method [76].…”
Section: Activated Carbonmentioning
confidence: 99%
“…Since Antonsson et al 1 selectively formed substituted cyclopentane derivatives in the presence of Pd(OAc) 2 -MnO 2 -benzoquinone as the catalyst in 1986, manganese dioxide (MnO 2 ) has been capturing more and more attention worldwide. As an important environment-benign transition metal oxide, MnO 2 has the advantages of abundant reserves, diverse morphology, rich crystalline forms and controllable grain sizes, and has a wide range of promising applications in electrode materials, [2][3][4] electrochromism, 5 catalysis, [6][7][8] biosensors, [9][10][11] etc.…”
Section: Introductionmentioning
confidence: 99%